Найти сумму корней: (х-4)(х-3)(х+1)(х+2)=24

manjester1 manjester1    3   10.09.2019 11:20    0

Ответы
stebone stebone  07.10.2020 05:10
(x-4)(x-3)(x+1)(x+2)=24

Перемножаем скобки (x-4)(x+2) и (x-3)(x+1)
(x^2-2x-8)(x^2-2x-3)=24

Замена:
x^2-2x=t \\ \\ (t-8)(t-3)=24 \\ t^2-11t=0 \\ t(t-11)=0 \\ t_1=0 \cup t_2=11

Обратная замена:
1) \\ x^2-2x=0 \\ x(x-2)=0 \\ x_1=0 \cup x_2=2 \\ \\ 2) \\ x^2-2x=11 \\ x^2-2x-11=0 \\ \frac{D}{4}=1+11=12=(2 \sqrt{3})^2 \\ x_1=1-2 \sqrt{3} \\ x_2=1+2 \sqrt{3}

И, наконец, сумма всех корней:
0+2+1-2 \sqrt{3}+1+2 \sqrt{3}=4

ответ: 4
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра